2021
DOI: 10.3389/fonc.2021.732782
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Carcinoma of the Endometrium: Evaluation of Prognostic Parameters in 27 Cases

Abstract: ObjectiveClear cell carcinoma (CCC) of the endometrium is an uncommon yet aggressive tumor. Few cohort studies are reporting the overall survival time of CCC patients. This study aimed to retrospectively analyze the clinicopathologic features, molecular characteristics and survival data of 27 endometrial CCC patients to improve the understanding of CCC.MethodsThe clinicopathologic features, molecular characteristics and survival data total of 27 CCC patients admitted to the BBMU affiliated hospital (Anhui, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
4
8
0
Order By: Relevance
“…In this study, ECCC patients with large tumor sizes and late T stages significantly enhanced the risk of death. These findings were consistent with a retrospective study that inferred that large tumor size and deep muscle invasion could be associated with poor prognosis among ECCC patients ( 17 ). Lymphatic metastasis is the main route of EC metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, ECCC patients with large tumor sizes and late T stages significantly enhanced the risk of death. These findings were consistent with a retrospective study that inferred that large tumor size and deep muscle invasion could be associated with poor prognosis among ECCC patients ( 17 ). Lymphatic metastasis is the main route of EC metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the findings of previous studies, we also observed that the median age at diagnosis of CCC was older compared to that of patients with endometrioid uterine adenocarcinoma [ 2 , 10 , 12 ]. Advanced-stage disease was observed in half of cases, and lymphovascular space involvement was encountered in 71 cases, indicating the aggressiveness of the histological subtype [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
“…Traditionally clear cell carcinoma has been considered as an aggressive type of endometrial cancer; however, among type II endometrial carcinomas it is considered as less aggressive compared to carcinosarcoma and undifferentiated sarcoma. Stage seems to be the most important factor that affects survival rates [19] followed by age and extent of myometrial invasion 7 although other co-factors such as Ki-67 index and P53 expression have been also proposed as potential predictors of survival [20].…”
Section: Discussionmentioning
confidence: 99%